2020
DOI: 10.1177/1010539520949421
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness Toward Coronavirus Disease-2019

Abstract: Background The emergence of the coronavirus disease 2019 (COVID-19) infection has become a global issue of concern. Since its occurrence, about 18 million cases have been reported globally and about 280 000 in the Kingdom of Saudi Arabia. Aim The aim of this study was to investigate the knowledge, attitudes, and practices of the general population toward COVID-19. Method A cross-sectional study was conducted. A questionnaire was built by the researchers that was composed of demographics, knowledge, attitudes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…These findings were consistent with the earlier published data on COVID-19 [13][14][15][16][17][18][19] in Saudi Arabia. The earlier publications [13][14][15][16][17][18][19] have mentioned the leading indicators of COVID-19 (fever, shortness of breath, cough, etc. ); its incubation period (2-14 days); the risk of COVID-19 in patients with associated diseases (hypertension, diabetes, and cancer, etc.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These findings were consistent with the earlier published data on COVID-19 [13][14][15][16][17][18][19] in Saudi Arabia. The earlier publications [13][14][15][16][17][18][19] have mentioned the leading indicators of COVID-19 (fever, shortness of breath, cough, etc. ); its incubation period (2-14 days); the risk of COVID-19 in patients with associated diseases (hypertension, diabetes, and cancer, etc.…”
Section: Resultssupporting
confidence: 93%
“…These articles have also stated that presently, there no active cure for COVID-19. The data of Table 2 and Table 3 is also in concurrence with the earlier studies [13][14][15][16][17][18][19], which discuss the initiation, spread, symptoms, & complications of COVID-19 in different populations. They also highlight the preventive measures to be followed, government strategic plans, and the importance of public education about the COVID-19.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Kharma, Alalwani, Amer, Tarakji, and Aws (2015) conducted a study from the perspective of the government to know the responsibility and concluded that healthcare providers were the primary persons who should educate public about the virus. Bdair, Alshloul, and Maribbay (2020) conducted a study with participation of 575 respondents aiming to know public perception, attitude and practices section of the public towards COVID-19. The findings showed that overall general public had adequate knowledge about the pandemic, however, there were negative tendencies and bad faiths (Bdair et al, 2020;Darnell, 2004) among the respondents towards the pandemic.…”
Section: Coronavirus: Behavior Of Pakistanis During Pandemic Peakmentioning
confidence: 99%
“…Bdair, Alshloul, and Maribbay (2020) conducted a study with participation of 575 respondents aiming to know public perception, attitude and practices section of the public towards COVID-19. The findings showed that overall general public had adequate knowledge about the pandemic, however, there were negative tendencies and bad faiths (Bdair et al, 2020;Darnell, 2004) among the respondents towards the pandemic. Chen, Xu, Paris, Reeson, and Li (2020) believed the people with greater awareness level had greater migration ties towards epicenter in Wuhan as compared to those who were with less information about the pandemic.…”
Section: Coronavirus: Behavior Of Pakistanis During Pandemic Peakmentioning
confidence: 99%